2015
DOI: 10.1038/srep08850
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of infectious malignant thrombocytopenia in Japanese macaques (Macaca fuscata) by SRV-4 after transmission to a novel host

Abstract: We discovered a lethal hemorrhagic syndrome arising from severe thrombocytopenia in Japanese macaques kept at the Primate Research Institute, Kyoto University. Extensive investigation identified that simian retrovirus type 4 (SRV-4) was the causative agent of the disease. SRV-4 had previously been isolated only from cynomolgus macaques in which it is usually asymptomatic. We consider that the SRV-4 crossed the so-called species barrier between cynomolgus and Japanese macaques, leading to extremely severe acute… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
24
0

Year Published

2015
2015
2020
2020

Publication Types

Select...
5
3

Relationship

6
2

Authors

Journals

citations
Cited by 16 publications
(24 citation statements)
references
References 56 publications
0
24
0
Order By: Relevance
“…We hypothesized that a substantial proportion of STLV-1-infected JMs might play a critical role as viral super-spreaders for frequent horizontal transmission and eventual high prevalence of STLV-1, possibly because of their abnormally high viral loads and incidence of poor humoral immune response against STLV-1. In fact, our recent incidence of an outbreak of infectious malignant thrombocytopenia in JMs by simian retrovirus type 4 (SRV-4) demonstrated that some of the monkeys developed asymptomatic SRV-4 infection with persistent viremia in the absence of SRV-4-specific antibody response and became viral super-spreaders [54], [55]. Taking this unexpected result into account, we evaluated ABTs and PVLs in the JM cohort.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that a substantial proportion of STLV-1-infected JMs might play a critical role as viral super-spreaders for frequent horizontal transmission and eventual high prevalence of STLV-1, possibly because of their abnormally high viral loads and incidence of poor humoral immune response against STLV-1. In fact, our recent incidence of an outbreak of infectious malignant thrombocytopenia in JMs by simian retrovirus type 4 (SRV-4) demonstrated that some of the monkeys developed asymptomatic SRV-4 infection with persistent viremia in the absence of SRV-4-specific antibody response and became viral super-spreaders [54], [55]. Taking this unexpected result into account, we evaluated ABTs and PVLs in the JM cohort.…”
Section: Resultsmentioning
confidence: 99%
“…We hypothesized that a substantial proportion of STLV-1-infected JMs might play a critical role as viral super-spreaders for frequent horizontal transmission and eventual high prevalence of STLV-1, possibly because of their abnormally high viral loads and poor humoral immune response against STLV-1. In fact, our recent incidence of an outbreak of infectious malignant thrombocytopenia in JMs by simian retrovirus type 4 (SRV-4) demonstrated that some of the monkeys developed asymptomatic SRV-4 infection with persistent viremia in the absence of SRV-4-speci c antibody response and became viral super-spreaders [54], [55]. Taking this unexpected result into account, we evaluated ABTs and PVLs in the JM cohort.…”
Section: Resultsmentioning
confidence: 99%
“…Data collected from certain groups of macaques or under certain conditions were excluded from the analysis, for example, from SRV infection experiments, 3 from SRV-positive macaques, and from macaques originating from areas other than Arashiyama (n = 76, age:10.0 ± 7.4 years old, range 0-25), Takahama (n = 86, age:…”
Section: Data Collection and Analysismentioning
confidence: 99%